Using Bourdieu in Critical Mediatization Research: Communicational Doxa and Osmotic Pressures in the Field of UN Organizations - Jansson, André (MedieKultur: Journal of media and communication research, 2015)
This article develops a Bourdieusian approach to mediatization. It is argued that the Bourdieusian theories of doxa and fields can make valuable contributions to a critical perspective on mediatization, one that moves beyond the divides between institutionalist, social-constructivist and materialist understandings (e.g., Bourdieu, 1972/1977). Mediatization is here seen as the historically growing dependence on media technologies and institutions within diverse social fields and settings. In order to establish the link between mediatization and Bourdieu’s theories (ibid.), the article introduces the concept of communicational doxa, which refers to the taken for granted communicational conventions and demands that regulate the inclusion of membership within a particular field. The article also shows how communicational doxa can be applied as an analytical concept. Findings from qualitative fieldwork carried out among highly mobile and skilled professionals within the field of UN organizations in Geneva, show how the autonomy of social agents is negotiated in relation to an increasingly mediatized communicational doxa.